Pelatihan English Verbs untuk Siswa SMK Negeri 5 Palu - Said, Mawardin M; Rita, Ferry; Syafar, Anshari; Maghfira, Maghfira; Ibmasiah Wardatun Islamiyah; Mawardin, Ide Ilmiah; Mawardin, Ilmuislami (Abimanyu: Journal of Community Engagement, 2023)
This Community Service aims at training students in using English Verbs. They hopefully can increase vocabulary especially their English verbs so that they can make sentences and communicate in that foreign language. They are motivated to master English verbs used in their daily activities to be able to communicate in that international language practically. Its speciic target is students having spirits to add English Verbsso that they can use them sustainably and influence their friends in using the English vocabulary in sentences. They easily communicate in the global language if have many its vocabularies. They also can be global learners. Communicative method is used to reach the objective. It is applied in interaction with the students. Its result is the Training of English Verbs for the students has been gone on well. Practical Ways of Learning English were explained to them who were also trained to increase the vocabulary and use them in sentences so that they can practice them even though have not veen fluent in making and expressing them. They hopefully master the English Verbs since all English sentences must have verbs.